Location decision of polluting firms and environmental policy - Francesco Prota; Francesco Contò (European Regional Science Association (ERSA), 2004)
The delocation of firms is often viewed as a major outcome of a stiff environmental policy. In this paper, we study the impact of a strict anti-pollution policy pursued by a government on domestic firms locational decisions and determine the main variables that interact with such a policy. Some preliminary welfare implications are also provided. Keywords: Environmental policy; Plant location; Imperfect competition. JEL classification: H7; R3; D4.
Keywords: H7; R3; D4; 330; Environmental policy; Plant location; Imperfect competition